What's Wrong with Designing People to Serve? - Chomanski, Bartek (Ethical theory and moral practice, 2019)
In this paper I argue, contrary to recent literature, that it is unethical to create artificial agents possessing human-level intelligence that are programmed to be human beings' obedient servants. In developing the argument, I concede that there are possible scenarios in which building such artificial servants is, on net, beneficial. I also concede that, on some conceptions of autonomy, it is possible to build human-level AI servants that will enjoy full-blown autonomy. Nonetheless, the main thrust of my argument is that, in building such artificial agents, their creators cannot help but evince an objectionable attitude akin to the Aristotelian vice of manipulativeness.